Production of single cell protein from pineapple peel waste using palmyrahtoddy yeast - Thiviya, P.; Kapilan, R.; Madhujith, T (University of Jaffna, 2019)
The disposal of fruit waste into environment poses health hazard for living beings. And also protein deficiency is becoming a major problem with the fast growing world population. The bioconversion of fruit wastes into single cell protein production is an innovative and alternative way to this direction. Therefore, this study was aimed to produce single cell proteins from pineapple peel using palmyrah (Borassus flabellifer) toddy yeast under liquid state fermentation system. Pineapple peel was collected, cleaned, washed and blended and physiochemical properties such as Total Soluble Solid (TSS), pH, moisture content, protein, fat and ash content were determined in dry weight basis. The extract of pineapple peel was filtered and diluted to 10% and autoclaved. The sterilized pineapple peel extract kept in sterilized conical flask in triplicates and inoculated with natural palmyrah toddy yeast and allowed for fermentation at 100 rpm for 48 hrs. The sediment was collected by centrifugation and oven dried and the dry weight was measured and the protein content was determined by using Kjeldahl method. The protein content of peel was 6.9%±0.06, the TSS, pH, moisture, fat and ash content of pineapple peel were 10.8%, 3.69, 84.68%±0.85, 0.86%±0.088 and 4.50%±0.30 respectively. The mean cell bio mass was 0.940±0.053 gram cell mass per 100 mL substrate and the crude protein content was significantly increased to 49.7% from 6.9% (7.2 times, dry weight basis). Therefore, locally available pineapple peel waste could be a good source for the production of protein-rich cell biomass using fermentation by natural toddy yeast of palmyrah.
Keywords: Liquid state fermentation; Palmyrah toddy yeast; Pineapple peel; Single cell protein